The impact of abnormal return towards dividend changes with private information as a moderating in Indonesia - Nurul Husna; Faisal Faisal (Proceedings of AICS - Social Sciences, 2017)
This study examines the impact of abnormal return towards dividend changes with private information as a moderating in Indonesia. The variables used in this study are abnormal return, private information, and dividend changes. Analysis model in this study is Moderated Regression Analysis (MRA). By using purposive sampling technique, there are 27 stocks as a research sample in Indonesia Stock Exchange 2013-2016. The result of this research shows that abnormal return has positive and significant impact towards dividend change. In other hand, private information in stock price has a negative and significant impact towards dividend change. The interaction analysis result shows that private information weakens the impact of abnormal return towards dividend changes. This study highlights private information in stock prices as an important determinant of dividend policy.